Cerebrovascular Reactivity and Central Arterial Stiffness in Habitually Exercising Healthy Adults - Miller, Kathleen B.; Howery, Anna J.; Harvey, Ronée E.; Eldridge, Marlowe W.; Barnes, Jill N. (Frontiers in Physiology, 2018)
Reduced cerebrovascular reactivity to a vasoactive stimulus is associated with age-related diseases such as stroke and cognitive decline. Habitual exercise is protective against cognitive decline and is associated with reduced stiffness of the large central arteries that perfuse the brain. In this context, we evaluated the age-related differences in cerebrovascular reactivity in healthy adults who habitually exercise. In addition, we sought to determine the association between central arterial stiffness and cerebrovascular reactivity. We recruited 22 young (YA: age = 27 ± 5 y, range 18–35 y) and 21 older (OA: age = 60 ± 4 y, range 56–68 y) habitual exercisers who partake in at least 150 minutes of structured aerobic exercise each week. Middle cerebral artery velocity (MCAv) was recorded using transcranial Doppler ultrasound. In order to assess cerebrovascular reactivity, MCAv, end-tidal carbon dioxide (ETCO2), and mean arterial pressure (MAP) were continuously recorded at rest and during stepwise elevations of 2%, 4%, and 6% inhaled CO2. Cerebrovascular conductance index (CVCi) was calculated as MCAv/MAP. Central arterial stiffness was assessed using carotid-femoral pulse wave velocity (PWV). Older adults had higher PWV (YA: 6.2 ± 1.2 m/s; OA: 7.5 ± 1.3 m/s; p<0.05) compared with young adults. MCAv and CVCi reactivity to hypercapnia were not different between young and older adults (MCAv reactivity, YA: 2.0 ± 0.2 cm/s/mmHg; OA: 2.0 ± 0.2 cm/s/mmHg; p=0.77, CVCi reactivity, YA: 0.018 ± 0.002 cm/s/mmHg2; OA: 0.015 ± 0.001 cm/s/mmHg2; p=0.27); however, older adults demonstrated higher MAP reactivity to hypercapnia (YA: 0.4 ± 0.1 mmHg/mmHg; OA: 0.7 ± 0.1 mmHg/mmHg; p<0.05). There were no associations between PWV and cerebrovascular reactivity (r = 0.00-0.39; p = 0.07–0.99). Our results demonstrate that cerebrovascular reactivity was not different between young and older adults who habitually exercise; however, MAP reactivity was augmented in older adults. This suggests an age-associated difference in the reliance on MAP to increase cerebral blood flow.